Issues in Spatio-temporal Database Systems: Data Models, Languages and Moving Objects - José Moreira (2002)
Spatio-temporal is a broad designation that may refer to a wide variety of systems dealing with the temporal evolution of spatial phenomena. Space and time are deeply ingrained in our commonsense reasoning patterns, and we have developed effective ways of taking their properties into account to manage their intrinsic complexity. It is therefore no surprise that representing and managing data where the temporal and spatial aspects are fundamental is a hard task. There are numerous application domains motivating the developments in this area. The problems posed by the integration of spatial and temporal dimensions of data require new solutions from database management systems. One application area which is receiving considerable attention concerns moving objects, represented as points in the spatial dimensions. This article presents an overview of spatio-temporal database systems, describing the main features of spatio-temporal objects and proposing a classification of spatiotemporal systems based on the properties of the represented objects. This classification allows understanding the complexity of the dynamics that underlie the temporal evolution of spatial phenomena. A survey of some issues in the spatio-temporal domain is also presented. The focus is on data models and languages for spatio-temporal database systems with moving object applications in mind. Open issues for future research, in the light of the features described as useful to being handled by spatiotemporal systems, are also identified.